Guillain-Barre: Clinical And Prognostic Features - Koçer, Abdulkadir (Fırat University, 2004)
Objective: Assessment of Guillain-Barre syndrome (GBS) cases in Dr. Lütfi Kirdar Kartal Education and Research Hospital over a 2-year period; investigation of a relationship between possible seasonality in GBS and the occurrence of preceding infections; and determination of distinctive characteristics and treatment protocols in patients with GBS. Materials and method: Records of patients with GBS admitted between 2001 and 2003 were evaluated retrospectively and prospectively Results: A total of 14 patients had a diagnosis of GBS. Patients above 50 years of age and men were more frequently found in the severely affected group. Men were more frequently affected than women. A preceding infection was reported in 78.5% of the cases. There was not any significance between therapy protocols and prognosis. Conclusion: The clinical and prognostic features of present study were the similar in previous reports. The severity increases with age and men are more frequently affected than women. The therapy protocols did not affect the prognosis in GBS. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Amaç: İki yılın üstü bir süreçte Dr.Lütfi Kırdar Kartal Eğitim ve Araştırma Hastanesi'ndeki GBS vakalarının değerlendirilmesi; GBS ile mevsimler ve öncesinde görülebilecek ilişkilerin değerlendirilmesi; GBS hastalarında ayırt edici özelliklerin ve tedavi protokollerinin belirlenmesi. Gereç ve yöntem: 2001 ve 2003 yılları arasında yatarak takipleri yapılmış hastaların kayıtları geriye ve ileriye dönük olarak değerlendirildi. Sonuç: Toplam 14 hasta GBS tanısı aldı. Elli yaş üstü ve erkek vakalarda hastalık daha ağır seyretmekteydi. Erkekler kadınlardan daha sıklıkla hastalığa maruz kalmaktaydı. GBS öncesi enfeksiyon olguların %78,5'inde rapor edildi. Tedavi protokolleri ve prognoz arasında istatistiksel bir ilişki yoktu. Bu çalışmadaki klinik ve prognostik veriler daha önce literatürde rapor edilenlere benzerdi. Hastalığın şiddeti yaş ile artmaktaydı ve erkekler hastalığa kadınlardan daha fazla maruz kalmaktaydı. Tedavi protokolleri GBS hastalarında prognozu etkilemedi. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Guillain-Barre: Klinik ve Prognostik Özellikler